Dengue presenting as gastric perforation: first case reported till date - Mandhane, Nisha; Ansari, Sharique; Shaikh, Tanveer; Deolekar, Sandesh; Mahadik, Abhishek; Karandikar, Sangram (International Journal of Research in Medical Sciences, 2017)
Gastrointestinal perforation is one of the common complications of various illness that is associated with high mortality and morbidity. The common sites of perforation in GIT (gastrointestinal tract) are stomach, duodenum, ileum and colon, but in dengue perforation in any of the above site is rare. Here we report an interesting case of gastric perforation that occurred in a young male patient post dengue fever. To our knowledge, this is the first such case of gastric perforation that occurred in our patient with dengue that we are reporting in the literature.